Engaged or Disengaged? Examining the Relationship Between Electoral Ambivalence and Indicators of Political Engagement in the 2012 U.S. Election. Issue 1 (1st January 2018) - Hmielowski, Jay D.; Kim, Sungsu; Hutchens, Myiah J.; Beam, Michael A.
ABSTRACT: This study uses uncertainty theories to examine the relationship between presidential electoral ambivalence and three political belief variables: internal efficacy, skepticism, and apathy. We propose that the relationship between ambivalence, which is an indicator of uncertainty, and information-seeking intentions should be mediated by our political belief variables. Our proposed model suggests that presidential electoral ambivalence is characteristic of a disengaged citizenry, with ambivalence correlating with lower levels of internal efficacy and skepticism in a cross-sectional analysis. We also found ambivalence associated with higher levels of apathy in this same analysis. Moreover, we found an over-time indirect effect of ambivalence on information seeking through internal efficacy.